Inovative and traditional use of ICT in teaching German language - Jitka Bláhová (Czech Pedagogical Society, 2010)
In the article, results are presented of international research projects whichsuggest that information and communication technologies (ICT) support innovativeconstructivist pedagogical approaches. These results are compared with research findingsacquired by the author of the text. A qualitative pedagogical research has beencarried out (using in-depth interviews and observation) among teachers of German atCzech upper-secondary comprehensive schools. The findings suggest that ICT do notfacilitate changes but rather - when used well - support innovative pedagogical approaches.ICT can make teaching and learning - both innovative and traditional - moreeffective if they provide lessons with an "added value".